Pension reform and couples' joint retirement decisions - Laura Hospido (IZA World of Labor, 2015)
Rising life expectancy and the growing fiscal insolvency of public pension systems have prompted many developed countries to raise the pension entitlement age. The success of such policies depends on the responsiveness of individuals to such changes. Retirement has increasingly become a decision made jointly by a couple rather than individually by one partner. The empirical evidence indicates that almost a third of dual-earner couples in Europe and the US coordinate their retirement decision despite age differences between partners. This joint determination of retirement has important implications for policies intended to reduce the burden of pension costs.
Keywords: J26; D10; C21; 330; social security incentives; pension entitlement ages; joint retirement